Parental Depression and Diabetes-Specific Distress After the Onset of Type 1 Diabetes in Children - Noser, Amy E. (Health Psychol, 2018)
OBJECTIVE: To examine trajectories of two types of type 1 diabetes (T1D) specific distress (i.e., daily T1D management and worries about the future and long-term complications) and the moderating role of parental depression in parents of children newly diagnosed with T1D. METHODS: A total of 126 families of five- to nine-year-olds with new-onset T1D enrolled in the study. One-hundred and twenty-five families completed study measures at baseline, 102 at six-month follow-up, and 89 at twelve-month follow-up. Parents completed measures of depression and T1D-specific distress concerning daily T1D management and worries about the future and long-term complications at baseline and at six- and twelve-month follow-ups. We used multilevel modeling to examine twelve month trajectories of daily and long-term T1D-specific distress and to examine if parental depression modified these trajectories. RESULTS: Results showed a significant reduction in daily T1D-specific distress from baseline to six-month follow-up and maintenance of daily T1D-specific distress from six- to twelve-month follow-up. The significant interaction of baseline parental depression and Time indicated that parents with depressive symptoms had a smaller reduction in daily T1D-specific distress from baseline to six-month follow-up compared to parents without depressive symptoms. Findings for long-term T1D-specific distress indicated that parents with depressive symptoms reported higher distress across all assessment points, with peak long-term T1D-specific distress for depressed parents occurring at six months. CONCLUSION: Many parents experienced significant T1D-specific distress for a period of time following their child’s initial diagnosis and this distress appears to be exacerbated by parental depressive symptoms.